Stratospheric age of air variations between 1600 and 2100. Issue 10 (18th May 2016) - Muthers, S.; Kuchar, A.; Stenke, A.; Schmitt, J.; Anet, J. G.; Raible, C. C.; Stocker, T. F.
Abstract: The current understanding of preindustrial stratospheric age of air (AoA), its variability, and the potential natural forcing imprint on AoA is very limited. Here we assess the influence of natural and anthropogenic forcings on AoA using ensemble simulations for the period 1600 to 2100 and sensitivity simulations for different forcings. The results show that from 1900 to 2100, CO2 and ozone‐depleting substances are the dominant drivers of AoA variability. With respect to natural forcings, volcanic eruptions cause the largest AoA variations on time scales of several years, reducing the age in the middle and upper stratosphere and increasing the age below. The effect of the solar forcing on AoA is small and dominated by multidecadal total solar irradiance variations, which correlate negatively with AoA. Additionally, a very weak positive relationship driven by ultraviolett variations is found, which is dominant for the 11 year cycle of solar variability. Key Points: Preindustrial AoA variations are small in comparison to the changes of the 20th and 21st centuries Strong volcanic eruptions cause the largest change in AoA on a time scale of several years The solar influence is small and differs for UV and non‐UV variations